What Causes Industry Agglomeration? Evidence from Coagglomeration Patterns - Ellison, Glenn; Glaeser, Edward L; Kerr, William R (American Economic Review, 2010)
Why do firms cluster near one another? We test Marshall's theories of industrial agglomeration by examining which industries locate near one another, or coagglomerate. We construct pairwise coagglomeration indices for US manufacturing industries from the Economic Census. We then relate coagglomeration levels to the degree to which industry pairs share goods, labor, or ideas. To reduce reverse causality, where collocation drives input-output linkages or hiring patterns, we use data from UK industries and from US areas where the two industries are not collocated. All three of Marshall's theories of agglomeration are supported, with input-output linkages particularly important. (JEL L14, L60, O33, R23, R32)